Divergent effects of urban particulate air pollution on allergic airway responses in experimental asthma: a comparison of field exposure studies - Wagner, James G (BioMed Central, 2012)
BACKGROUND: Increases in ambient particulate matter of aerodynamic diameter of 2.5 μm (PM(2.5)) are associated with asthma morbidity and mortality. The overall objective of this study was to test the hypothesis that PM(2.5) derived from two distinct urban U.S. communities would induce variable responses to aggravate airway symptoms during experimental asthma. METHODS: We used a mobile laboratory to conduct community-based inhalation exposures to laboratory rats with ovalbumin-induced allergic airways disease. In Grand Rapids exposures were conducted within 60 m of a major roadway, whereas the Detroit was located in an industrial area more than 400 m from roadways. Immediately after nasal allergen challenge, Brown Norway rats were exposed by whole body inhalation to either concentrated air particles (CAPs) or filtered air for 8 h (7:00 AM - 3:00 PM). Both ambient and concentrated PM(2.5) was assessed for mass, size fractionation, and major component analyses, and trace element content. Sixteen hours after exposures, bronchoalveolar lavage fluid (BALF) and lung lobes were collected and evaluated for airway inflammatory and mucus responses. RESULTS: Similar CAPs mass concentrations were generated in Detroit (542 μg/m(3)) and Grand Rapids (519 μg/m(3)). Exposure to CAPs at either site had no effects in lungs of non-allergic rats. In contrast, asthmatic rats had 200% increases in airway mucus and had more BALF neutrophils (250% increase), eosinophils (90%), and total protein (300%) compared to controls. Exposure to Detroit CAPs enhanced all allergic inflammatory endpoints by 30-100%, whereas inhalation of Grand Rapids CAPs suppressed all allergic responses by 50%. Detroit CAPs were characterized by high sulfate, smaller sized particles and were derived from local combustion sources. Conversely Grand Rapids CAPs were derived primarily from motor vehicle sources. CONCLUSIONS: Despite inhalation exposure to the same mass concentration of urban PM(2.5), disparate health effects can be elicited in the airways of sensitive populations such as asthmatics. Modulation of airway inflammatory and immune responses is therefore dependent on specific chemical components and size distributions of urban PM(2.5). Our results suggest that air quality standards based on particle speciation and sources may be more relevant than particle mass to protect human health from PM exposure.